The Technology in ESP: The Use of Telegram Application in Teaching English for Islamic Study: Technology in ESP: The Use of Telegram Application in Teaching English for Islamic Study - Irma, Irma; Latifa, Ammang; Hasmiati, Hasmiati (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2021)
Teaching ESP on today students needs the application of technology. Hence, this study discusses about integrating technology in teaching English for Islamic study at University of Muhammadiyah Parepare by Using Telegram Application. The objective of this study is to measure whether the use of telegram application in integrating technology in ESP class has a significant difference on students’ achievement and to investigate the students’ perception about the use of telegram application in integrating technology in teaching English for Islamic study at University of Muhammadiyah Parepare. This study used mixed method which combine the quantitative and qualitative data. Based on the result of quantitative data analysis, it is indicated that the use of telegram application in integrating technology in teaching English for Islamic study not produce significant difference on students’achievement. It is proved by the result of comparing t-test value and t-table value. The t-test value (1.455) is not higher than t-table value (2.262). However, the result of qualitative data analysis shows that the use of telegram application in teaching English for Islamic study produce positive perception of students. It means that the use of telegram has the possitive effect in integrating technology in teaching English for Islamic study.